'Frustrated' hydrogen-bonded self-associated systems as templates towards DNA incorporated nanostructure formation. Issue 1 (2nd January 2018) - Gumbs, Tamrin L.; White, Lisa J.; Wells, Neil J.; Shepherd, Helena J.; Hiscock, Jennifer R.
Abstract: Herein, we present the synthesis of a thymine nucleobase-appended 'frustrated' monomer, which exhibits self-association in DMSO solutions through the formation of hydrogen bonds. This self-association process has been explored in both competitive DMSO solutions and the solid state, using a combination of NMR and single crystal X-ray diffraction techniques. The self-associative equilibria within the solution state are balanced in such a way that the hydrogen bond donating and accepting thymine residue present within the monomeric structure is free to coordinate further guest species such as the complimentary DNA base adenine. The adenine simulants, 2-aminopyridine and 2, 6-diaminopyridine have been used to explore the potential of these self-associated structures towards the coordination of complimentary DNA base pairs. Abstract :